Renovação Urbana, Segregação e Mercado Habitacional - Bógus, Lúcia M. M. (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 1990)
Contribution to the analysis of urban space-population relationships based on the case study of Satte Intervention through implementation of the urban regeneration project - Project CURA - in an area in the municipality of São Paulo. This project set in motion a rapid process of increased real estate values, causing the substitution on the poorest group of residents by a higher income social group, in addition to causing a growing process of “ verticalization” in construction. These changes also lead to questions of property ownership, showing that the ways of acess to urban land are an important factor for retention or expulsion of the resident social groups in a certain area, when this area increases in value